Silence in Transit: Women's Experiences of Sexual Harassment and Bystander’s Action in Public Transportation (Khwopa Journal, 2026)
Every day, thousands of women in Kathmandu commute by public buses to work and college. For many of them, this simple activity comes with an invisible burden of fear due to the prevalence of sexual harassment. This qualitative study explores the experiences of sexual harassment among women commuters in Kathmandu's public buses, focusing on the forms of harassment, its effects, and the critical role of bystanders. Through in-depth interviews with ten female participants who commute daily for educational and occupational purposes, this study reveals that physical harassment is the most common form, under the cover of crowded buses and manufactured ambiguity. As such, female travelers face anxiety, lost confidence, and a growing reluctance to use public transportation at all. The most painful part is the silence of those around them, the bystanders, leaving victims feeling invisible, ashamed, and as if it were a normal incident. However, those who spoke up against such incidents were all female bystanders, indicating shared vulnerability and sisterhood among them. Even a person speaking up can diffuse the incident, boost the morale of the victims, and change the perpetrator's intention of the perpetrator. Addressing this issue demands not just better policies and infrastructure, but a society willing to stand up for one another.